Windows 8.1 step by step - Rusen, Ciprian Adrian; Ballew, Joli. (2013)
A guide to the concepts and features of Windows 8.1 discusses such topics as the start screen, apps, Internet Explorer 11, SkyDrive, multimedia, networking, and security.--
Includes index.
Keywords: Microsoft Windows (Computer file); Windows (Computer programs); Operating systems (Computers); Windows 8.1.